Playing With Knives: The Socialization of Self‐Initiated Learners. Issue 3 (May 2016) - Lancy, David F.
Abstract : Since Margaret Mead's field studies in the South Pacific a century ago, there has been the tacit understanding that as culture varies, so too must the socialization of children to become competent culture users and bearers. More recently, the work of anthropologists has been mined to find broader patterns that may be common to childhood across a range of societies. One improbable commonality has been the tolerance, even encouragement, of toddler behavior that is patently risky, such as playing with or attempting to use a sharp‐edged tool. This laissez faire approach to socialization follows from a reliance on children as "self‐initiated learners." In this article, the ethnographic literature that shows why children are encouraged to learn without prompting or guidance and how that happens is reviewed.